Поняття історичної балади та епічна народна пісня «Дівчина Косовка» - Милошевич-Джорджевич, Н. (Народна творчість та етнологія, 2012)
The paper examines the problem of the genre of the song «A Kosova-girl» from the collection of Vuk Karadžić. The author examines the last research, devoted to the problem mentioned, presents her own method of analysis, and comes to the conclusion that the song reveals the characteristics, typical for Serbian epic poesy as a genre.